2013
DOI: 10.1021/ef3017392
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Study of Asphaltene Deposition

Abstract: Asphaltenes are a solubility class of petroleum crude oil that can destabilize and deposit in both upstream and downstream processes. In this study, asphaltene deposits were generated in metal capillaries by heptane addition to crude oils, and it was found that deposition is caused by submicrometer asphaltene aggregates. Deposits were generated at heptane concentrations above and significantly below the instantaneous onset point. Analysis of the results reveals that the governing factor controlling the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
215
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(227 citation statements)
references
References 33 publications
(96 reference statements)
11
215
0
1
Order By: Relevance
“…At higher temperature, the colloidal asphaltenes are small in amount and tend not to form strong associations, because the resins effectively disperse the colloids (Branco et al, 2001;Hoepfner et al, 2013;Maqbool et al, 2011). This is because the part of asphaltenes is dissolved leaving enough mass of the resins and oil to keep the remaining smaller aggregates of asphaltenes well peptized in the oil at higher temperature.…”
Section: Fig 6 Peptizability Of Asphaltenes Versus Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…At higher temperature, the colloidal asphaltenes are small in amount and tend not to form strong associations, because the resins effectively disperse the colloids (Branco et al, 2001;Hoepfner et al, 2013;Maqbool et al, 2011). This is because the part of asphaltenes is dissolved leaving enough mass of the resins and oil to keep the remaining smaller aggregates of asphaltenes well peptized in the oil at higher temperature.…”
Section: Fig 6 Peptizability Of Asphaltenes Versus Temperaturementioning
confidence: 99%
“…Much of the research has been driven by the tendency of asphaltenes to aggregate, precipitate and deposit onto surfaces (Arciniegas and Babadagli, 2014;Hoepfner et al, 2013;Mullins et al, 2007;Spiecker et al, 2003;Maqbool et al, 2011). Deposit formation in crude oil processing can be attributed to various factors but asphaltenes are generally considered as main precursors of deposit formation on heat transfer surfaces in crude oil processing (Hoepfner et al, 2013;Murphy and Campbell, 1992;Wiehe, 2006). The presence of asphaltenes on heat transfer surfaces further favors fouling of equipment because asphaltenes are more prone to attach to already coked surfaces than a clean metallic alloy surface (Asprino et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltene deposition can appear at various stages of oil production, transportation and processing, leading to arterial blockages of wellbores, pipelines, separators, heat exchangers and other surface facilities [1][2][3]. As oil flows in wellbores or pipelines, due to the change in pressure (p), temperature (T) and oil composition, asphaltene precipitation usually takes place producing particles.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,11 In order to establish the consistent and clear terminology, several terms (e.g., "deposition" and "precipitation") which will be used in this paper are defined. 12,13 Firstly, "precipitation" refers to the whole process of asphaltenes converting from stable conditions to the aggregation or precipitation of asphaltene in micron level. Secondly, "deposition" will be used to describe the suspended precipitated asphaltene detached from the crude oil and deposited in the solid-surface (e.g., the porous media).…”
mentioning
confidence: 99%
“…14 Simultaneously, most of the laboratory experiments and field results investigated that the effect of the pressure, temperature, and oil composition on AP are all important factors. 12,15,16 Zendehoudi, S. et al found that the contribution of the temperature, pressure, and oil composition to the AP amount accounts for 37%, 36%, and 27%, respectively. 18 In addition, for the actual oilfield, the operating pressure has significant impacts on the AP phenomenon during the process of primary oil recovery.…”
mentioning
confidence: 99%